2000
DOI: 10.1006/dbio.2000.9732
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of cre to the Foxg1 (BF-1) Locus Mediates loxP Recombination in the Telencephalon and Other Developing Head Structures

Abstract: The use of genetics to study the development of the telencephalon and derivatives such as the cerebral cortex has been limited. The telencephalon begins to form midway through gestation, and targeted mutations in genes suspected of playing roles in its development often lead to early phenotypes that preclude analysis of their role at later stages. This problem can be circumvented using a Cre/loxP recombination system. A mouse line was produced in which cre was targeted to the Foxg1 (BF-1) locus, a gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
631
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 500 publications
(657 citation statements)
references
References 25 publications
26
631
0
Order By: Relevance
“…Our steroid responsive Cre line yields nearly 100% recombination of reporter transgene in astrocytes throughout brain but there was significant Cx43 protein left when Cx43 f/f /hGFAP-CreER T2 mice were induced. Other investigators have observed variability in the recombination of different Cre responder transgenic lines when crossed to the same Cre expressing line (Hara-Kaonga et al, 2006;Hebert and McConnell, 2000;Vooijs et al, 2001). Investigators using a GLAST-CreER T2 knockin stated that recombination of the Cx43::lacZ locus had lower efficiency in cortex than ROSA26R (15.5% vs 30%; Mori et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Our steroid responsive Cre line yields nearly 100% recombination of reporter transgene in astrocytes throughout brain but there was significant Cx43 protein left when Cx43 f/f /hGFAP-CreER T2 mice were induced. Other investigators have observed variability in the recombination of different Cre responder transgenic lines when crossed to the same Cre expressing line (Hara-Kaonga et al, 2006;Hebert and McConnell, 2000;Vooijs et al, 2001). Investigators using a GLAST-CreER T2 knockin stated that recombination of the Cx43::lacZ locus had lower efficiency in cortex than ROSA26R (15.5% vs 30%; Mori et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous Foxg1-Cre mice described by Hebert and McConnell (2000) resulted in a null mutant phenotype for Foxg1. Foxg1-Cre heterozygotes were maintained on a mixed 129/C57BL/6 background resulting from mating with other strains such as Gt(ROSA)26Sor tm2Sho (The Jackson Laboratory, Bar Harbor, ME) (Mao et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…In mice harboring a targeted mutation of the Foxg1 gene (Hebert and McConnell, 2000), we observe initial specification of some olfactory placode cells but a failure of those cells to proliferate and differentiate into mature olfactory neurons. Mice lacking Foxg1 ultimately fail to form all olfactory structures, an effect we ascribe to defects in the early olfactory placode, with a subsequent increase in apoptosis.…”
Section: Introductionmentioning
confidence: 91%
“…In addition, while the isthmus that expresses both Fgf3 (Powles et al, 2004) and Fgf8 (Crossley and Martin, 1995) next to Foxg1-Cre, (Hebert and McConnell, 2000) is reduced but still present in the Fgf3 Ϫ/Ϫ and Fgf8 TelKO single mutants, it does not form in the Fgf3 Ϫ/Ϫ ;Fgf8 TelKO double mutant indicating a requirement for Fgf3 and Fgf8 for establishment or maintenance of the isthmus (Fig. 3D and Supp.…”
Section: Fgf3 Does Not Cooperate With Fgf8 During Forebrain Patterninmentioning
confidence: 98%
“…The following mouse lines used in this study have been described previously: Fgf3 Ϫ/Ϫ knockout mutants (Alvarez et al, 2003), mutants carrying a conditional (Fgf8 flox ) or a null allele (Fgf8 d2,3 ) for Fgf8 (Meyers et al, 1998), mouse lines in which cre has been targeted to the Foxg1 locus (BF-1) (Hebert and McConnell, 2000), and transgenic mice which express lacZ under the control of Fgf3 regulatory sequences (Powles et al, 2004b). To obtain mouse mutants that lacked Fgf8 expression in the telencephalon (Fgf8 TelKO ), we crossed animals carrying a Fgf8 null allele and the Foxg1-Cre transgene (Fgf8 d2,3/ϩ ;Foxg1 Cre/ϩ ) with animals carrying a conditional Fgf8 allele (Fgf8 flox/flox ) to obtain Fgf8 flox/d2,3 ; Foxg1 Cre/ϩ (Fgf8 TelKO ) mutants as previously described (Storm et al, 2003).…”
Section: Experimental Procedures Transgenic Micementioning
confidence: 99%